2014
DOI: 10.1155/2014/682647
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Seismic Behavior of Container Crane Structures by Shake Table Tests and Mathematical Modeling

Abstract: This paper is concerned with the verification of mathematical modeling of the container cranes under earthquake loadings with shake table test results. Comparison of the shake table tests with the theoretical studies has an important role in the estimation of the seismic behavior of the engineering structures. For this purpose, a new shake table and mathematical model were developed. Firstly, a new physical model is directly fixed on the shake table and the seismic response of the container crane model against… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 14 publications
0
13
0
3
Order By: Relevance
“…Kohama [13] and Miyata [14] et al analyzed the dynamic response characteristics of a crane structure under the action of a rare earthquake by performing model experiments and numerical simulation. Azeloglu et al [15] verified the mathematical modeling of container cranes under earthquake loadings with shake table test results; the developed mathematical model reasonably represented the dynamic behavior of the crane structure both in time and frequency domains. Inadomi et al [16] carried out a series of the vibration tests of a prototype wharf and calculation simulation of the wharf and the crane to study the vibration characteristics of the structures; they observed that the crane exerted an insignificant effect on the vibration of the wharf when the acceleration was small (not exceeding 20 gal).…”
Section: Literature Reviewmentioning
confidence: 85%
“…Kohama [13] and Miyata [14] et al analyzed the dynamic response characteristics of a crane structure under the action of a rare earthquake by performing model experiments and numerical simulation. Azeloglu et al [15] verified the mathematical modeling of container cranes under earthquake loadings with shake table test results; the developed mathematical model reasonably represented the dynamic behavior of the crane structure both in time and frequency domains. Inadomi et al [16] carried out a series of the vibration tests of a prototype wharf and calculation simulation of the wharf and the crane to study the vibration characteristics of the structures; they observed that the crane exerted an insignificant effect on the vibration of the wharf when the acceleration was small (not exceeding 20 gal).…”
Section: Literature Reviewmentioning
confidence: 85%
“…e main response form of QCC is the bending vibration of the leg around z-axis under seismic condition; thus, the content of Section 2.2 can be referred to design the cross section size of the leg. e sectional dimensions of landside leg 2 and the z-axis moment of inertia are 186.7 mm 2 and 3.42e5 mm 4 , respectively. However, it should be noted that the size of the similarity leg is difficult to achieve in practice.…”
Section: Eory Of Dynamicmentioning
confidence: 99%
“…However, it is very difficult to manufacture a complete dynamic similar model of QCC in the above-scale ratio range as the geometric size of each component in QCC cannot be magnified or reduced in equal proportions. Although the method of adding mass [2,3], amplifying input acceleration peak [4] and adjusting the section moment of inertia [5,6], was used to satisfy the similarity design, these methods have their limitations; for example, the method of adding mass has a negative influence on the QCC stability of overall structure.…”
Section: Introductionmentioning
confidence: 99%
“…The authors showed that the simulated model is sufficient to perform dynamic time history analysis for evaluating the overall behavior, including uplift and derailment phenomena. Azeloglu et al [3] investigated the seismic behavior of the container crane by shake table test (using a 1:20 scaled container crane) and a mathematical model, and also concluded that the dynamic behavior, including in the time and frequency domains, of the crane structure could be represented by the mathematical model. Kanayama et al [4] carried out studies on the dynamic response of cranes by a series of shaking table tests (using 1/25 and 1/8 scaled crane models).…”
Section: Introductionmentioning
confidence: 99%